2012
DOI: 10.1111/j.1741-3729.2011.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative and Positive Caregiving Experiences: A Closer Look at the Intersection of Gender and Relationship

Abstract: Using data from the 2004 wave of the National Long-Term Care Survey, we examined how negative and positive caregiving experiences differ by caregivers’ gender and relationship to care recipients. We further considered how their caregiving experiences are affected by caregivers’ demographic characteristics, care recipients’ problem behavior and dependency, caregivers’ involvement, reciprocal help from care recipients, and social support available for caregivers. We found that female and adult-child caregivers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 44 publications
8
144
1
3
Order By: Relevance
“…Zarit et al 1986;Lüdecke et al's 2012), there is also research on caregiving men which has shown that norms of gender may get in the way of caregiving men's willingness to use formal support because caregiving and masculinity are not synonymous (e.g. Coe and Neufeld 1999;Lin et al 2012;Sanders 2007).…”
Section: Caregiving Men In Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Zarit et al 1986;Lüdecke et al's 2012), there is also research on caregiving men which has shown that norms of gender may get in the way of caregiving men's willingness to use formal support because caregiving and masculinity are not synonymous (e.g. Coe and Neufeld 1999;Lin et al 2012;Sanders 2007).…”
Section: Caregiving Men In Previous Researchmentioning
confidence: 99%
“…Most studies within this key idea include both women and men (e.g. Fromme et al 2005;Hash 2006;Bookwala 2009;Sugiura et al 2009;Dunér 2010;Lin et al 2012;Lüdecke et al 2012;Hosseinpoor et al 2013;Friedemann and Buckwalter 2014) but there are some studies that focus only on women (e.g. Mendez-Luck et al 2008, Silverman 2015.…”
Section: Literature Based On Empiricalmentioning
confidence: 99%
“…Family members are the most common source of care provider (informal caregivers) for the disabled. Female family members are more often engaged as informal caregivers, which may be a result of their social role to nurture [22]. Furthermore, our sample showed that caregivers are mostly undereducated and unemployed.…”
Section: Discussionmentioning
confidence: 88%
“…Caregivers may feel useful and satisied, and they may view caring as a way to pay back for the help they received from their patients in the past [8].…”
Section: Positive Efects Of Caregivingmentioning
confidence: 99%
“…It is estimated that 36 million people provide unpaid care to a family member who is age 65 or older, while about 80% of these are spouses or adult children. Family caregivers usually provide more than 20 h of care per week to older adults [8].…”
Section: Introductionmentioning
confidence: 99%